A Review of Suicide Prevention Bills in Philippine Legislation and their Comparison with R.A. 11036: The Mental Health Act - Quintos, Mark Anthony M. (Silliman Journal, 2024)
The passage of R.A. 11036 (Mental Health Act) has been hailed as a victory for mental health advocates. While the law itself is a step in the right direction, it cannot be considered as a law that wholly confronts the problem of suicide. Rather, bills focusing on suicide prevention remain pending in Congress with no certainty as to their eventual fates. This study reviews the bills filed before the 13th up to the 19th Congress of the Philippines (2004 to 2024) and identifies the different steps they propose for suicide prevention. These proposed steps are compared with the provisions of R.A. 11036 to determine whether the existing law is sufficient to deal with the suicide problem or whether there is a need for further legislation specific to suicide prevention. Results showed that there were 32 suicide bills proposed in a span of 20 years. These bills can be divided into 7 themes and they stipulated 19 different steps for suicide prevention – out of which only 12 were partially covered by the Mental Health Act.